EFFECTS OF COVER CROPS AND TILLAGE SYSTEMS ON SOIL PHYSICAL PROPERTIES OF COGONGRASS LAND - Bambang Gonggo Murcitro; Bandi Hermawan; Dwi Anggraeni (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2005)
Amendment of soil physical properties on cogongrass field is required for crop production. Objective of this study was determine the physical properties of the soil that was previously populated by cogongrass as affected by cover crops and tillage systems. A split plot design was used to allocate the combinations of conventional tillage and no-tillage system with 5 species of cover crops. Results showed that the properties of soil physic were not affected by cover crop species. No-tillage resulted in lower bulk density, but higher porosity and organic content, compared to conventional tillage.